Sp140L functions as a herpesvirus restriction factor suppressing viral transcription and activating interferon-stimulated genes - Jana M. Cable; Wiyada Wongwiwat; Jenna C. Grabowski; Robert E. White; Micah A. Luftig (Proceedings of the National Academy of Sciences, 2025)
Herpesviruses, including Epstein–Barr virus (EBV) – a human oncogenic virus and essential trigger of multiple sclerosis – must bypass host DNA-sensing mechanisms to establish lifelong, latent infection. Therefore, herpesviruses encode viral proteins to disrupt key host factors involved in DNA sensing and viral restriction. The first viral latency protein expressed, EBNA-LP, is essential for transformation of naïve B cells and establishment of viral gene expression, yet its role in evading host defenses remains unclear. Using single-cell RNA sequencing of EBNA-LP Knockout (LPKO)-infected B cells, we reveal an antiviral response landscape implicating the “speckled proteins” as key cellular restriction factors countered by EBNA-LP. Specifically, loss of Sp100 or the primate-specific Sp140L reverses the restriction of LPKO, suppresses a subset of canonically interferon-stimulated genes, and restores transcription of essential latent viral genes and cellular proliferation. Notably, we also identify Sp140L as a restriction target of the herpesvirus saimiri ORF3 protein, implying a role for Sp140L in immunity to other diverse DNA viruses. This study reveals Sp140L as a restriction factor that we propose links sensing and transcriptional suppression of viral DNA to an Interferon-independent innate immune response, likely relevant to all nuclear DNA viruses.